THE EFFECTS OF DISTILLATION TEMPERATURE AND PLASTIC LOADING ON THE IMPROVEMENT OF WASTE-DERIVED BIO-OIL PROPERTIES - Irawansyah, Herry; Amrullah, Apip; Prayogi, Syafaâ€™at; Alfahri, Syahriza (Universitas Mataram, 2023)
Since plastic and food waste are both types of non-lignocellulosic biomass, these must be handled and managed correctly to avoid pollution problems and damage to the environment. Bio-oil, made from recycled materials, including plastic and food waste, is one focus of these attempts. The co-pyrolysis method is being investigated in this study as a technique of recycling plastic waste and food waste to produce biofuels with reduced environmental impact. In terms of energy efficiency, bio-oil is unequal to other fuels like coal or natural gas because of its high acidity, high oxygen content, and low thermal stability. Therefore, a vacuum distillation process is required to improve bio-oil quality by adjusting the distillation temperature from 300 to 350 OC and the percentage of plastic waste used from 30 to 50%. The bio-oil was analyzed using a Gas Chromatography-Mass Spectrometer (GC-MS). The general compound showed that acids (60%) and alcohols (20%) were the most prevalent chemical compounds, followed by phenol (4%), aldehyde (14%), aliphatic (5%), Furan (14%), and ketones (11%) at maximum temperature (350 oC) for 30-50% plastic waste. Meanwhile, the final product is affected by temperature and plastic waste (PET) ratio factors. At 350 Â°C and a plastic waste addition of 50%, the highest bio-oil yield is 45%.